The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016 IEEE Online Conference on Green Communications (OnlineGreenComm) 2016
DOI: 10.1109/onlinegreencom.2016.7805402
|View full text |Cite
|
Sign up to set email alerts
|

Architecture exploration of multi-source energy harvester for IoT nodes

Abstract: International audienceWireless sensor networks are constrained by their energy supply. In order to relief this constraint, scavenging ambient energy from the environment has been considered. However, most existing energy harvesting devices rely on a single energy source, potentially reducing the sensor reliability. In this paper, we present an architecture for multi-source energy harvesting, aimed at low cost and easy integration with existing wireless sensors. Unlike existing architectures, our solution relie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…Figure 1B). Sustainability can be achieved through either technical improvements via means such as optimization of energy efficiency (Gleonec et al, 2017;Mazinani and Davarzani, 2017), or innovative soft management/incentivebased approaches (Bakker and Ritts, 2018). Most of the reviewed studies identified with a sustainability element were associated with explicit and direct human benefits, such as monitoring a particular resource (e.g., Wada et al, 2007), protecting property or livelihoods (e.g., Lopes Pereira et al, 2014) or were agricultural in nature and focused on resource use to maximize yields (e.g., Geipel et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1B). Sustainability can be achieved through either technical improvements via means such as optimization of energy efficiency (Gleonec et al, 2017;Mazinani and Davarzani, 2017), or innovative soft management/incentivebased approaches (Bakker and Ritts, 2018). Most of the reviewed studies identified with a sustainability element were associated with explicit and direct human benefits, such as monitoring a particular resource (e.g., Wada et al, 2007), protecting property or livelihoods (e.g., Lopes Pereira et al, 2014) or were agricultural in nature and focused on resource use to maximize yields (e.g., Geipel et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Appl. 2020, 10, 11 3 of 11 overall efficiency. Moreover, diodes are non-linear devices that work as a variable impedance that changes with input power itself, making it more difficult to design an efficient matching network.…”
Section: Design Methods and Optimizationmentioning
confidence: 99%
“…In recent years, the great use of low-power autonomous systems and sensors [1][2][3][4][5][6] increased the need for self-sustainable devices, which are capable of harvesting and using energy from the environment, particularly for those that need a continuous power supply (such as human health monitoring systems) [7][8][9][10][11][12][13]. These devices, such as low-voltage front-ends for photomultiplier [4] or monitoring systems for buildings with a low power consumption [6], can use energy scavenged from the environment, which is typically poor but enough to ensure the system functionality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new trend in energy harvesting is to provide the node with the ability to be powered by several energy sources [4], [5]. In such multi-source energy harvesting systems, dedicated EMs must be designed to operate with the different sources.…”
Section: Introductionmentioning
confidence: 99%